2019
DOI: 10.1016/j.biocon.2019.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the response of fishes to recreational fishing over 30 years within a fringing coral reef reserve network

Abstract: While there are numerous studies that have used no-take marine reserves (NTMRs) to understand the effects of commercial fishing, much less is known about the influence of NTMRs in regions subject to recreational fishing. We used meta-analysis to synthesise data from 4,444 samples from 30 years (1987-2017) of fish 7 surveys, inside and outside a large network of NTMRs in the Ningaloo Marine Park, Western Australia, 8 where the major fishing activities are recreational. The data were collected by different agenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 64 publications
2
21
1
Order By: Relevance
“…Not all MPAs have the same effects, as demonstrated in this study and others (e.g. Cresswell et al, ; Edgar et al, ), and it is important to understand what drives these heterogeneous effects of MPAs. Many factors can contribute to the outcomes of a protected area, such as harvesting regulations, level of enforcement, age, size and nearby habitat (Edgar et al, ).…”
Section: Discussionsupporting
confidence: 50%
“…Not all MPAs have the same effects, as demonstrated in this study and others (e.g. Cresswell et al, ; Edgar et al, ), and it is important to understand what drives these heterogeneous effects of MPAs. Many factors can contribute to the outcomes of a protected area, such as harvesting regulations, level of enforcement, age, size and nearby habitat (Edgar et al, ).…”
Section: Discussionsupporting
confidence: 50%
“…There is evidence that this trend may have existed for some time as our estimates of counts and biomass of emperors at Mandu in 2007 (our first observations) were somewhat lower than those from earlier studies 11,13 . The most commonly landed emperor at Ningaloo, Lethrinus nebulosus , was only observed on our transects twice since 2010 (it was recorded during each survey from 2007 to 2010); it would have been desirable to analyse trends in abundance of this species, but the very low numbers of individuals observed precluded such analyses.…”
Section: Discussioncontrasting
confidence: 59%
“…Here, we evaluate trends in the abundance (measured as density and biomass) of fish in the Ningaloo Marine Park (NMP), located within the Ningaloo Coast World Heritage Area, north-western Australia. Several previous studies have indicated that sanctuary zones (SZ, equivalent to IUCN Category II) within the park contain higher abundances of some fishes than zones which allow recreational fishing 1113 , but our ability to detect long-term trends is hampered, because these studies have used different techniques (visual census and baited video), have been carried out at different locations, or use relative abundance. We surveyed fish assemblages of shallow reefs in the majority of years from 2007–2016; we then sought to determine whether our surveys yielded evidence of increasing or decreasing trends during that period, and if so, to quantify what the trend was, and if it varied between management zones designed to control fishing.…”
Section: Introductionmentioning
confidence: 99%
“…CSIRO’s 1982 and 1997 data were integrated into more recent trawl, tow video and sled sampling to document fishes of the Dampier and Montebello Australian Marine Parks [ 30 ]. Other studies of fish assemblages of the NWS have focused on areas of specific biological interest, for example the Rowley Shoals [ 31 – 33 ], Ningaloo Reef World Heritage Area [ 34 , 35 ], Browse Island [ 20 , 36 ], Sahul Banks [ 37 ] and Rankin Bank [ 38 ] The broader NWS also supports the most valuable commercial finfish fisheries in Western Australia, the Pilbara trap, line and trawl fisheries and the Northern Demersal Scalefish Fishery, which are worth more than $10 million annually with a catch of 3000–4000 tonnes per year [ 39 ]. These fisheries have also been a focal point of research documenting the catch and biology of fish fauna of the NWS, in particular the high market value snappers, emperors and cods on which the fishery is based [ 15 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%